ANALISIS RESPON MAHASISWA FISIKA UNIVERSITAS JEMBER TERHADAP VIRTUAL LABORATORIUM SCRATCH POKOK BAHASAN GERAK MELINGKAR - Salsabila Tazkia Aulia; Berlian Shoofa Kamila; Sal Salbila Wardahtuz Tarita Putri; Firdha Kusuma Ayu Anggraeni; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2022)
The purpose of this study is to analyze the response of students of physics education at the University of Jember to a virtual laboratory assisted by scratch on the subject of circular motion. The method used is descriptive and the sample is 93 students of the Physics Education Class of 2021/2022. The data collection technique is in the form of student response questionnaires made using google forms. Based on the results of the research that has been done, the average percentage result is 83.1%, which is included in the very feasible category. Thus, it can be concluded that the virtual scratch laboratory on the subject of circular motion is very suitable to be used during physics practicum.